Internalisasi Nilai Agama Dalam Pendidikan Anak Usia Dini - Taqiyudin Subky; Tri Mulat (STAI Sufyan Tsauri Majenang, 2021)
The background of this research is that children are a mandate from Allah swt given to parents who must be educated to become human beings who believe and worship Him. In this position, the role of educators is strongly supported by educational methods in imparting education to children. The problem of this research is what values can be used in internalizing religious values into children's education. The results of this study are expected to be used to add to the scientific treasures, especially in the method of children's education.This research is library research, namely literature review through library research using qualitative data, namely information data in the form of verbal sentences, not symbols of numbers or numbers. The approach used is a philosophical pedagogical approach, an approach which is a careful analysis of reasoning about a problem and a deliberate and systematic preparation of a point of view that forms the basis of an action.